SUSTAINABLE DEVELOPING FISHERIES IN THE INTEGRATED MANAGEMENT FRAMEWORK ON THE WEST COASTAL ZONE OF THE TONKIN GULF - Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2009)
Located on the North-West of East sea, the Tonkin Gulf is enclosed by Vietnamese and Chinese coasts with the surface 124.500 km 2 and 1950 km sorrowing area. In the Vietnamese part, in the Tonkin Gulf contains over 3000 islands as Halong Bay, Catba islands, Bai Tu Long Bay etc. The Tonkin Gulf is very important area, there are many economical activities are going as caching, marine transport, mine exploitations and marine tourism. By this important, very long time ago, the fisheries study in the Tonkin Gulf was proceed. The results show that in the Tonkin Gulf are very high biodiversity, richness ecosystems giving potent ion for marine ecotourism. But, the fishery stock concentrates on the coastal zone and very sensible and declining. By this reasons, the strategy of sustainable fisheries exploitation is exploiting parallel with the protection. The works are resolved only by connecting closely between plan exploitation with the coastal zone integrated management. The main objects are sustainable exploitation, sustainable marinecuture and marine economy